Influence of implant angulation and implant number on the accuracy of definitive casts - Abhay Kiran Narayane; Suhana Shamsuddeen; Swati Kharat; Tabish Rashidi; Aachut Pandav; Manoj Kumar Thakur (Wolters Kluwer Medknow Publications, 2021)
Background: The present study determined the effect of implant angulation and implant number on the dimensional precision of implant definitive casts. Materials and Methods: Three definitive casts with implant analogs placed in a triangular pattern were made from dental stone. Group I was control group, Group II in which implant numbers 1 and 3 were at 5° convergence to the implant number 2. Group III in which implant numbers 1 and 3 are at 5° divergence to the implant number 2. Group IV in which implant numbers 1 and 3 are at 10° convergence to the implant number 2. Implant analogs were secured in all the definitive casts with cyanoacrylate. Three open tray impressions of the definitive cast were obtained and poured in Type IV dental stone. Coordinates in the three planes were measured at implant analog top surface and base of the cast using a fine tip measuring stylus. The data were aligned and angular differences between implant analog vectors from definitive and duplicate casts were measured. Results: There was a significant correlation between dental implant number and dental implant angulation (P < 0.05). There was a significant result when comparing the effect of the parallel group from 5° divergence and 10° convergence groups. A significant results while comparing the parallel group with 5° divergence and 10° convergence was obtained whereas while comparing 5° divergence, 5° divergence, and 10° convergence a nonsignificant difference was obtained (P > 0.05). Conclusion: Close proximity of implant angulation toward right-angled direction results in higher precision of implant.